Analysing sentences : an Introduction to English syntax - Burton-Roberts, Noel , 1948- (Learning about language)
"This highly successful text has long been considered the standard introduction to the practical analysis of English sentence structure. It covers key concepts such as constituency, category and functions, and also uses tree diagrams throughout to help the reader visualise the structure of sentences"-- Provided by publisher